The Carving & Healing of a Wound: Linguistic homelessness and disidentification as survival - Daniela Rodriguez A. (InterAlia, 2023)
Building on the work of chicana theorist Gloria Anzaldúa and queer theorist José Esteban Muñoz this paper analyses and discusses the affective component of language for those whose first language has been overshadowed by a second language. I ask how language affects the self’s sense of identity/belonging, the possibility for communicating/accessing queerness, and what linguistic or poetic tools can be employed to empower the self. Following the tradition of feminist thought that assumes that the personal is political, I write from personal experiences. As a Colombian-born migrant in Sweden, I explore how the overshadowing of my mother tongue (Spanish) by Swedish (as the language with the perceived highest social and cultural value in Swedish society) has impacted on my self-image, sense of identity, self-worth and queerness.